Food Ethics Education (Integrating Food Science and Engineering Knowledge Into the Food Chain ;, 2018)
Although many consider professional ethics in the food supply chain an essential topic that should be covered in any degree program, few higher education institutions currently include a module on ethics in their study programs. Instead, ethics is taught in tandem to the core curriculum and is often embedded in the contents of other modules rather than treated as a subject in its own right. Ethics, however, is important enough to warrant a different teaching and educational approach. This book provides support for development of a course in ethics for food studies education. The book is divided into 3 sections, each containing several chapters: Section 1 includes chapters that identify and discuss several ethical issues along the food chain, with particular attention given to issues in the food industry and in consumer behavior; Section 2 includes chapters that present the basis of a code of conduct in the food profession, as well as descriptions of existing codes of conduct for food industry and food scientist professionals. These include codes for the ethics of publishing, and also ethics in risk communication; Section 3 includes chapters based on case studies with examples of teaching approaches currently used in teaching food ethics. These approaches are easy to implement and have already been tested and confirmed as successful examples that engage students in this topic.